Divine Justice, Free Will, and Moral Consequences in Alisher Navoi’s Khamsa and John Milton’s Paradise Lost - Nigora , Zakirova (The Lingua Spectrum, 2025)
This article explores the themes of divine justice, free will, and moral consequences as presented in two monumental works of literature: Alisher Navoi’s Khamsa and John Milton’s Paradise Lost. By comparing these epic texts, this paper seeks to understand how both authors address the concept of justice from a divine perspective, the role of human free will in determining moral outcomes, and the consequences of moral actions. The analysis highlights the differences and similarities in how these poets portray the relationship between God and humanity, as well as how their cultural and religious backgrounds influence their literary representations. Through a comparative lens, the article examines the moral frameworks presented in both texts and assesses how the authors use narrative structures and characters to illustrate their respective philosophies on divine justice and free will.